THE EFFECT OF PBL ON STUDENTS’ MATHEMATICAL LITERACY BASED ON KOLB’S LEARNING STYLES - Cahyadi, Rendy Tri; Pujiastuti , Heni; Rafianti, Isna (Universitas Muhammadiyah Metro, 2026)
This study aims to examine the effect of the PBL model on students’ mathematical literacy skills and to describe variations in literacy achievement based on Kolb’s learning styles. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Pretest–Posttest Control Group Design. The sample consisted of 51 eighth-grade students from SMP Kebangsaan, South Tangerang City, divided into an experimental class and a control class. Data were collected using a mathematical literacy test based on the indicators of formulating, employing, interpreting, and reasoning, as well as Kolb’s learning style questionnaire. Data analysis involved descriptive and inferential statistics, including prerequisite tests, an independent sample t-test, and N-Gain analysis. The results indicated a significant difference in mathematical literacy skills between students taught using the PBL model and those taught using an expository approach (0,027 < 0.05). Furthermore, the N-Gain analysis revealed that students in the PBL class demonstrated higher improvement in mathematical literacy skills compared to the control class. Descriptive analysis based on learning styles showed variations in literacy achievement across learning style types, although no inferential analysis was conducted. These findings suggest that the PBL model is effective in enhancing students’ mathematical literacy skills. Penelitian ini bertujuan untuk menganalisis pengaruh model PBL terhadap kemampuan literasi matematis siswa SMP serta mendeskripsikan variasi capaian literasi matematis berdasarkan gaya belajar David Kolb. Penelitian menggunakan pendekatan kuantitatif dengan metode eksperimen semu dan desain Nonequivalent Pretest–Posttest Control Group Design. Sampel penelitian terdiri atas 51 siswa kelas VIII SMP Kebangsaan Kota Tangerang Selatan yang terbagi ke dalam kelas eksperimen dan kelas kontrol. Data dikumpulkan melalui tes kemampuan literasi matematis berbasis indikator formulating, employing, interpreting, dan reasoning, serta angket gaya belajar Kolb. Analisis data dilakukan menggunakan statistik deskriptif dan inferensial, meliputi uji prasyarat, uji independent sample t-test, dan analisis N-Gain. Hasil penelitian menunjukkan bahwa terdapat perbedaan signifikan kemampuan literasi matematis antara siswa yang memperoleh pembelajaran PBL dan pembelajaran ekspositori (0,027 < 0,05), serta peningkatan kemampuan literasi matematis siswa pada kelas PBL lebih tinggi dibandingkan kelas kontrol berdasarkan analisis N-Gain. Analisis deskriptif berdasarkan gaya belajar menunjukkan adanya variasi capaian literasi matematis antar tipe gaya belajar, meskipun tidak dianalisis secara inferensial. Temuan ini menunjukkan bahwa PBL efektif digunakan untuk meningkatkan kemampuan literasi matematis siswa SMP.